Some combinations: Praxis, multimodal art research and complex environments - Williams, Quinten Edward (My University, 2014)
This project (“theoretical component” and “practical component”) explores a philosophical understanding as well as my experiential understandings of environments as complex systems (Cilliers 2005, 2007; Deleuze & Guattari 1987, 1994; Morin 1999, 2007, 2008). I have understood the engagements in environments as being co-constitutive of assemblages (Deleuze & Guattari 1987). Through the production of works of art and its processes (Deleuze & Guattari 1994) in different modalities (Cole & Masny 2009) as praxis (Deleuze 2004a), these undertakings can be understood as creative arts research. It could be construed that this project moves around three areas, namely, those of creative arts research, environments understood through complexity, and Johannesburg city as a complex environment. In a sense, however, this dissertation is only one entry point into an embedded research project, which has been engaged with materials and bodies in environments. This is a complex area (Cilliers 2005, 2007; Morin 1999, 2007), an area which deals with heterogeneity and becoming (Deleuze and Guattari 1987, 1994).